2019
DOI: 10.1038/s41598-018-37745-7
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic demyelinated CNS lesions exhibit opposite elastic properties

Abstract: Increased deposition of extracellular matrix (ECM) is a known inhibitor of axonal regrowth and remyelination. Recent in vitro studies have demonstrated that oligodendrocyte differentiation is impacted by the physical properties of the ECM. However, characterization of the mechanical properties of the healthy and injured CNS myelin is challenging, and has largely relied on non-invasive, low-resolution methods. To address this, we have employed atomic force microscopy to perform micro-indentation measurements of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 56 publications
(65 reference statements)
1
52
0
Order By: Relevance
“…Another feature of reactive ASTRs is increased deposition of ECM proteins. Upon toxin-induced demyelination, ASTRs transiently deposit several ECM proteins, including CSPGs and fibronectin, which add to resolve injury and promote recovery [221,[235][236][237][238][239]. The composition of the ECM affects OPC behavior; fibronectin increases OPC proliferation and migration and inhibits OPC differentiation [236,[239][240][241][242][243][244][245][246][247][248], while CSPGs inhibit OPC proliferation, migration and differentiation [239,[249][250][251][252][253].…”
Section: Astrocyte Diversity and Remyelinationmentioning
confidence: 99%
“…Another feature of reactive ASTRs is increased deposition of ECM proteins. Upon toxin-induced demyelination, ASTRs transiently deposit several ECM proteins, including CSPGs and fibronectin, which add to resolve injury and promote recovery [221,[235][236][237][238][239]. The composition of the ECM affects OPC behavior; fibronectin increases OPC proliferation and migration and inhibits OPC differentiation [236,[239][240][241][242][243][244][245][246][247][248], while CSPGs inhibit OPC proliferation, migration and differentiation [239,[249][250][251][252][253].…”
Section: Astrocyte Diversity and Remyelinationmentioning
confidence: 99%
“…4 c). Of interest, transient ECM remodeling plays an important role in successful remyelination [ 5 , 57 , 74 , 75 ]. The extracellular matrix proteome, or the “matrisome” consists of core and associated proteins [ 76 ] and a heatmap of abundantly expressed matrisome-core and matrisome-associated genes that differed significantly (FDR < 0.05) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These lesions, as suggested by the name of the disease, are stiffer than the normal CNS (sclerotic). [ 24 ] The effect that this increased stiffness might have on the generation of OLs from resident OPCs has been addressed in a number of studies. [ 4,20 ] These have shown that OPCs are mechanosensitive, with substrate stiffness altering differentiation via signaling through the YAP/transcriptional coactivator with PDZ‐binding motif (TAZ) pathway.…”
Section: Discussionmentioning
confidence: 99%